Strategic Effectiveness: Search - Solve - Create - Participate - Evaluate - in the Middle School Students’ Achievement on Arabic - Salih, Noor Adeeb; Jabor, Salah Fakher (Journal of Ecohumanism, 2024)
This study aims to determine the effectiveness of various strategies—search, solve, create, participate, and evaluate—in improving middle school students’ achievement in Arabic. The experimental group was designed with partial control, following quasi-experimental design phases to meet research objectives. Before implementing the experiment, the researcher ensured comparable competencies between the two groups, constructed an Arabic achievement test, and confirmed its psychometric qualities. After implementation, the researcher also conducted additional tests.The study discovered that using the search-solve-create-participate-evaluate strategy in teaching Arabic raises academic achievement among sixth-grade middle school students. The experimental group outperformed the control group in the Arabic language achievement test. This demonstrates the effectiveness of the search-solve-create-participate-evaluate strategy in enhancing middle school students’ Arabic language achievement.